Why the war on drugs in sport will never be won. Issue 1 (December 2015) - Smith, Aaron; Stewart, Bob
Abstract Recent exposes of drug use in sports suggest that doping might be more problematic than doping-control test results reveal. A zero-tolerance (ZT) model, which aims to eliminate the use, has dominated the thinking of sport's policy makers over the last 15 years. In light of the limitations associated with ZT-based policy, we propose an alternative policy, one based on controlled use and harm reduction principles. We argue that substance control policies underpinned by harm reduction (HR) principles of social utility and public value will deliver superior social outcomes. First, a harm reduction approach better accommodates the competitive realities of sports and the impact of elite sports' emphasis on performance at all costs. Second, HR prioritises athlete welfare over sport and brand reputation. Finally, while appreciating the regulatory and risk management responsibilities of sports' governing bodies, the HR model offers greater space to the athlete's right to privacy, and right to personal autonomy.